PATH-08. THE IVY GLIOBLASTOMA PATIENT ATLAS - A NOVEL CLINICAL AND RADIO-GENOMICS RESOURCE FOR EARLY PHASE CLINICAL TRIAL DESIGN AND INTERPRETATION. (5th November 2018) - Ligon, Keith; Lupo, Janine; Molinaro, Annette; Block, Shannon; Charbonneau, Sarah; Geduldig, Jack; Stemmer-Rachamimov, Anat; DeAngelis, Lisa; Yong, William; Schultz, Nikolaus; Young, Robert; Huang, Raymond; et al.
Abstract: Newly diagnosed GBM represents a population of increased focus in early phase clinical trials. However, a key limitation of current genomic databases of GBM, such as TCGA, is that patient populations eligible for inclusion in these databases exhibit inherent biases and exhibit limitations on the quality of clinical and imaging data available for integration with genomics. To address these limitations and to better represent the genomics of patient populations commonly enrolled to early phase clinical trials, we prospectively consented and enrolled GBM patients to the Ivy Foundation Glioblastoma Patient Atlas Project. A total of 1591 patients from 7 participating sites of the Ben and Catherine Ivy Foundation Consortium for Early Phase Clinical Trials were consented to the project and clinical data was entered into a centrally managed clinical trials database. Overall 658 subjects had pre- and post-surgical imaging centrally reviewed and recorded and 387 subjects had sufficient tissue for completion of targeted exome sequencing of approximately 500 cancer causing genes (Oncopanel or Impact). More than 308 subjects had a complete set of genomics, imaging, and clinical data, including TMZ/RT use, KPS, progression, and steroid use. Histopathological features, MGMT, and IDH mutation status were also annotated. Of the subjects with full clinical data, 171 had expired by the time of last analysis of the cohort. Genomic and clinical characteristics unique to the early phase clinical trial population compared to TCGA and other cohorts of GBM were identified and radio-genomic and other advanced population-based analyses were performed. All clinical, genomic and imaging data are being utilized to create an Ivy cBio Portal for sharing of this rich dataset within the neurooncology community.